Fractional Effective Quark-Antiquark Interaction in Symplectic Quantum Mechanics - R. R. Luz; M. Abu-Shady; G. X. A. Petronilo; A. E. Santana; R. G. G. Amorim (Advances in High Energy Physics)
Considering the formalism of symplectic quantum mechanics, we investigate a two-dimensional nonrelativistic strong interacting system, describing a bound heavy quark-antiquark state. The potential has a linear component that is analyzed in the context of generalized fractional derivatives. For this purpose, the Schrödinger equation in phase space is solved with the linear potential. The ground state solution is obtained and analyzed through the Wigner function for the meson cc¯. One basic and fundamental result is that the fractional quantum phase-space analysis gives rise to the confinement of quarks in the meson, consistent with experimental results.